From brothel to zakah - Abdul Majid, Nurul Huda; Tahir, Agoos Munalis; Kasim, Munirah; Abu Bakar, Mahyuddin (2017)
Ali was in dilemma. How would he help his childhood friend, Mastura emancipated from brothel. Was there any way in Islam to free a person in captivity? Ali remembered her story. It was five years ago when Mastura was just 17 years old, she got married to Hasnan, a stranger that she just met for two months. Mastura leaved Alor Setar for Kuala Lumpur to be with her husband. Unfortunately, her husband who was supposed to be her protector in joys and sorrows, sold her to brothel in Lorong Haji Taib. In hesitant, she was forced to become prostitute without any pay. The brothel had very strict security and only provided her with room, foods and clothes. Two years later, she got pregnant and gave birth to a baby girl named Sarah. According to Mastura, she broke out from the brothel with the help of her regular client. Escaped from brothel, Mastura hoped that she could start her life all over again in her hometown, Alor Star. That was when Ali met Mastura, where she begged for help from him.Ali had been working as the manager of Asnaf Development and Zakat Distribution Division in Lembaga Zakat Negeri Kedah (LZNK) for 10 years. He thought of how would zakah be of help to Mastura. Ali brought the matter to his boss, Haji Zakaria Othman, who had asked him to study other states practice.